Biomaterial scaffolds for treating osteoporotic bone - Sterling, Julie A. (2014)
Healing fractures resulting from osteoporosis or cancer remains a significant clinical challenge. In these populations, healing is often impaired not only due to age and disease, but also by other therapeutic interventions such as radiation, steroids, and chemotherapy. Despite substantial improvements in the treatment of osteoporosis over the few decades, osteoporotic fractures are still a major clinical challenge in the elderly population due to impaired healing. Similar fractures with impaired healing are also prevalent in cancer patients, especially those with tumor growing in bone. Treatment options for cancer patients are further complicated by the fact that bone anabolic therapies are contraindicated in patients with tumors. Therefore, many patients undergo surgery to repair the fracture, and bone grafts are often used to stabilize orthopaedic implants and provide a scaffold for ingrowth of new bone. Both synthetic and naturally occurring biomaterials have been investigated as bone grafts for repair of osteoporotic fractures, including calcium phosphate bone cements, resorbable polymers, and allograft or autograft bone. In order to re-establish normal bone repair, bone grafts have been augmented with anabolic agents, such as mesenchymal stem cells (MSC) or recombinant human bone morphogenetic protein-2 (rhBMP2). These developing approaches to bone grafting are anticipated to improve the clinical management of osteoporotic and cancer-induced fractures.